Detecting Cytosolic Peptide Delivery with the GFP Complementation Assay in the Low Micromolar Range. Issue 50 (30th October 2015) - Schmidt, Samuel; Adjobo‐Hermans, Merel J. W.; Wallbrecher, Rike; Verdurmen, Wouter P. R.; Bovée‐Geurts, Petra H. M.; van Oostrum, Jenny; Milletti, Francesca; Enderle, Thilo; Brock, Roland
Abstract: Transfection of cells with a plasmid encoding for the first ten strands of the GFP protein (GFP1‐10) provides the means to detect cytosolic peptide import at low micromolar concentrations. Cytosolic import of the eleventh strand of the GFP protein either by electroporation or by cell‐penetrating peptide‐mediated import leads to formation of the full‐length GFP protein and fluorescence. An increase in sensitivity is achieved through structural modifications of the peptide and the expression of GFP1‐10 as a fusion protein with mCherry. Abstract : Peptide‐based GFP complementation : Cells expressing the GFP1‐10 GFP fragment (gray circle) are electroporated or penetrated with GFP‐11 (gray squares) conjugated by a linker (blue line) to a cell‐penetrating peptide (orange line), thereby resulting in delivery into the cytosol and GFP complementation and fluorescence (green circle).